Evaluation of streamflow changes due to climate variation and human activities using the Budyko approach - Kazemi, H.; Sarukkalige, Ranjan; Badrzadeh, H. (SPRINGER, 2019)
This paper presents a successful application of the Budyko approach to assess the streamflow changes in the Harvey Catchment, Western Australia, due to climate variation and human activities. For cross-validation, results from the Budyko approach were compared with the HBV hydrology model. A hybrid estimation-optimisation algorithm (ANN-PSO) was used to automatically calibrate the HBV model to increase the accuracy by preventing human errors and to reduce the time-consuming process associated with the calibration. Results from the both approaches indicate climate change is the dominant factor in streamflow reduction in the Harvey Catchment with 55% attribution. Additionally, the Budyko approach was applied to estimate future streamflow changes in the Harvey River. Results show a significant reduction in streamflow (i.e., 38–58%) by 2100. The use of the Budyko approach to reliably ascribe the impacts of climate change and human activities to variation in streamflow was upheld. The Budyko approach, which uses limited hydrological data, can also be adopted as an alternative to hydrological modelling in predicting future streamflow changes, especially in ungauged catchments and catchments with limited hydrological information.